A case of lung adenocarcinoma with a novel CD74‐ROS1 fusion variant identified by comprehensive genomic profiling that responded to crizotinib and entrectinib. Issue 18 (28th July 2021) - Hashiguchi, Mizuha Haraguchi; Sato, Takashi; Watanabe, Rinako; Kagyo, Junko; Matsuzaki, Tomohiko; Domoto, Hideharu; Kato, Terufumi; Nakahara, Yoshiro; Yokose, Tomoyuki; Hiroshima, Yukihiko; Shiomi, Tetsuya
Abstract: ROS1 rearrangements are found in 1–2% of patients with non‐small‐cell lung cancer. The detection of the rearrangements is crucial since clinically effective molecular targeted drugs are available for them. We present a case of lung adenocarcinoma with a previously unknown ROS1 ‐ CD74 fusion variant, CD74 exon 3 fused to ROS1 exon 34, which was not detected by a conventional RT‐PCR‐based test for ROS1 fusion gene detection but identified by hybrid capture‐based next‐generation sequencing. This tumor responded to crizotinib initially and to entrectinib after relapse with brain metastasis, indicating the oncogenic activity of this novel fusion variant. Abstract : We present a case of lung adenocarcinoma with a novel ROS1 ‐ CD74 fusion variant, CD74 exon 3 fused to ROS1 exon 34, which was not detected by a conventional RT‐PCR‐based testing but identified by hybrid capture‐based next‐generation sequencing. This tumor responded to crizotinib initially and to entrectinib after relapse with brain metastasis, indicating the oncogenic activity of this novel fusion variant.